2014
DOI: 10.5430/wje.v4n5p40
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Physics Teaching in Senior High Schools

Abstract: This study sought to examine the activities that go on in physics classrooms in Senior High Schools in Ghana. Specifically, the study sought to investigate the pattern of interaction and instructional methods used for teaching physics and level of coverage of physics syllabus. The survey design was employed for the study in which questionnaire was used for data collection. Participants for the study were physics teachers and final year physics students. Findings from the study suggest that classroom interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…They added that, physics teachers do not have the needed content knowledge and pedagogical preparation for teaching physics effectively. This is supported by a study in Ghana by Buabeng et al [17] who concluded that "most of the physics teachers do not have academic qualification and/or certificate in education. What this means is that these teachers may lack the pedagogical knowledge and they are unfamiliar with the teacher actions that support and promote student learning".…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…They added that, physics teachers do not have the needed content knowledge and pedagogical preparation for teaching physics effectively. This is supported by a study in Ghana by Buabeng et al [17] who concluded that "most of the physics teachers do not have academic qualification and/or certificate in education. What this means is that these teachers may lack the pedagogical knowledge and they are unfamiliar with the teacher actions that support and promote student learning".…”
Section: Introductionmentioning
confidence: 71%
“…It has been shown that physics content is the least covered among three elective science subjects of biology, chemistry and physics in SHS in Ghana. In a study conducted by Buabeng et al [17], it was shown that, the level of coverage for physics in an academic term as indicated by teachers was about 80% with only 4.8% of the teachers being able to achieve 100% coverage of the content for the term. This implies that physics teachers may not be able to cover all the content so they believe reducing the content will improve the teaching and learning of physics in senior high schools Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations